Byzance apres Byzance revisited: Changing perspectives on Europe’s Byzantine heritage - Kitromilides, Paschalis M. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1995)
[Δε διατίθεται περίληψη / no abstract available]